Self-Organized Metapattern Resonance in Visual-Kinetic Feedback Loops: Interstitial Insights into the Emergence of Consciousness through Chaotic Systems - San Miguel, Jordan (Northridge Review, 2024)
By simultaneously performing kinemic analysis and image reconstruction of visual hallucinations using fMRI monitoring cortical activity of adolescent brains under the infuence of heavy psychoactive substances, we aim to uncover relationships which govern the organization of these data over time. Specifcally, we plan to conduct detailed statistical analysis of the correlation between the choice of particular kinemics and perception of their corresponding visual hallucinations in order to monitor the progression of their mutual efects on each other and shed light on the nature of the self-reinforcing visual-kinesic relationship over time. In doing so, we hope to provide a theoretical basis for further analysis of the role which positive feedback loops play in the emergence of consciousness.